TRPC4 and GIRK channels underlie neuronal coding of firing patterns that reflect Gq/11-Gi/o coincidence signals of variable strengths - Tian, Jin Bin (2022)
Transient receptor potential canonical 4 (TRPC4) is a receptor-operated cation channel codependent on both the Gq/11-phospholipase C signaling pathway and Gi/o proteins for activation. This makes TRPC4 an excellent coincidence sensor of neurotransmission through Gq/11- and Gi/o-coupled receptors. In whole-cell slice recordings of lateral septal neurons, TRPC4 mediates a strong depolarizing plateau that shuts down action potential firing, which may or may not be followed by a hyperpolarization that extends the firing pause to varying durations depending on the strength of Gi/o stimulation. We show that the depolarizing plateau is codependent on Gq/11-coupled group I metabotropic glutamate receptors and on Gi/o-coupled γ-aminobutyric acid type B receptors. The hyperpolarization is mediated by Gi/o activation of G protein-activated inwardly rectifying K+ (GIRK) channels. Moreover, the firing patterns, elicited by either electrical stimulation or receptor agonists, encode information about the relative strengths of Gq/11 and Gi/o inputs in the following fashion. Pure Gq/11 input produces weak depolarization accompanied by firing acceleration, whereas pure Gi/o input causes hyperpolarization that pauses firing. Although coincident Gq/11-Gi/o inputs also pause firing, the pause is preceded by a burst, and both the pause duration and firing recovery patterns reflect the relative strengths of Gq/11 versus Gi/o inputs. Computer simulations demonstrate that different combinations of TRPC4 and GIRK conductances are sufficient to produce the range of firing patterns observed experimentally. Thus, concurrent neurotransmission through the Gq/11 and Gi/o pathways is converted to discernible electrical responses by the joint actions of TRPC4 and GIRK for communication to downstream neurons.